Prevalence of hypertension and diabetes in health workers of Jabalpur and Dindori: a brief study - Sengar, Gautami Singh; Singh, Kritika; Dey, Arpan; Shrivastava, Suyesh (International Journal of Research in Medical Sciences, 2023)
Background: Hypertension and Diabetes comprises a major part as precursor of crucial diseases like cardiovascular diseases. Cardiovascular diseases are cause of death of around 17 million people per year globally, which includes 30% of total deaths. Methods: The present study was conducted to observe the prevalence of hypertension and diabetes among health care worker groups, in different health care centres at Bajag block of Dindori district & Indian council of Medical Research- National Institute for research in Tribal Health (ICMR-NIRTH) Jabalpur during the study period from January 2022 to June 2022. The participants were subjected to anthropometric measurements, Blood pressure & blood glucose level measurements and they also responded to the detailed questionnaire. Results: The 95 health care workers including nurses, technicians, ASHA workers, ANMs, which were assessed in the present study have shown 14.7% diabetes and 38% hypertension. Conclusions: The present study is important step towards the wellbeing of health workers as very few efforts were made to observe the prevalence of NCDs in health workers of rural areas.